2021
DOI: 10.3389/fmicb.2021.724345
|View full text |Cite
|
Sign up to set email alerts
|

Blood Meals With Active and Heat-Inactivated Serum Modifies the Gene Expression and Microbiome of Aedes albopictus

Abstract: The Asian “tiger mosquito” Aedes albopictus is currently the most widely distributed disease-transmitting mosquito in the world. Its geographical expansion has also allowed the expansion of multiple arboviruses like dengue, Zika, and chikungunya, to higher latitudes. Due to the enormous risk to global public health caused by mosquitoes species vectors of human disease, and the challenges in slowing their expansion, it is necessary to develop new and environmentally friendly vector control strategies. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 106 publications
0
3
0
Order By: Relevance
“…Equipped with electronic temperature controls and a blood reservoir, this system regulates the feeding environment to mimic natural conditions [ 21 ]. The Hemotek feeding system is relevant for the standardization of the infectious agent dose, vector competence, and pathogen transmission studies [ 103 , 104 , 105 ]. It has been instrumental in various pathogen transmission studies, such as studies on malaria transmission [ 106 ], evaluating the effectiveness of different blood sources for rearing Ae.…”
Section: Artificial Feeding Systems For Vectorsmentioning
confidence: 99%
“…Equipped with electronic temperature controls and a blood reservoir, this system regulates the feeding environment to mimic natural conditions [ 21 ]. The Hemotek feeding system is relevant for the standardization of the infectious agent dose, vector competence, and pathogen transmission studies [ 103 , 104 , 105 ]. It has been instrumental in various pathogen transmission studies, such as studies on malaria transmission [ 106 ], evaluating the effectiveness of different blood sources for rearing Ae.…”
Section: Artificial Feeding Systems For Vectorsmentioning
confidence: 99%
“…That same year another metatranscriptomic study analyzed total RNA extracted from dissected abdomens of Ae. albopictus females fed with sugar and human blood containing either normal or heat-inactivated serum, to evaluate the effect of heat inactivation on gene expression in the mosquitoes, and on the bacterial and viral components of their microbiome (Calle-Tobón et al 2021). The authors found that at least 600 host genes showed a modified expression profile when mosquitoes were fed with normal vs. heat-inactivated-containing blood, and that the bacterial community changed at 6 hours post-feeding.…”
Section: Metatranscriptomic Studies In Mosquitoesmentioning
confidence: 99%
“…Recent works, using a combination of culturing and metagenomic sequencing approaches ( Gusmão et al, 2010 ; Boissière et al, 2012 ; Osei-Poku et al, 2012 ; Coon et al, 2014 , 2016 ; Sharma et al, 2014 ; Dickson et al, 2017 ), have supported these findings, also identifying fungi such as Saccharomyces (yeast) in mosquitoes ( Ricci et al, 2011 ; Coon et al, 2016 ; Muturi et al, 2016a ; Bozic et al, 2017 ; Tawidian et al, 2021 ). The composition and diversity of the mosquito gut microbiome are influenced by various factors, including breeding site ( Boissière et al, 2012 ; Tawidian et al, 2021 ), blood meal ( Wang et al, 2011 ; Muturi et al, 2016a ; Calle-Tobón et al, 2021 ), developmental stages ( Dickson et al, 2017 ), presence of pathogens ( Muturi et al, 2016a ; Trzebny et al, 2021 ), and mosquito species ( Muturi et al, 2016a , 2016b ; Hegde et al, 2018 ). However, some microbial communities are common to mosquitoes across species or geolocation ( Osei-Poku et al, 2012 ).…”
Section: The Mosquito Microbiomementioning
confidence: 99%